Factors Influencing Documentation Based on NANDA NIC NOC and SDKI, SLKI, SIKI - Neneng Ilah Rohilah; Muhammad Hadi; Melati Fajarini (UIMA Press, 2022)
Background: The development of nursing care standards in accordance with nursing laws issued by professional organizations, namely PPNI. These standards of care are the Indonesian Nursing Diagnosis Standards (IDHS), the Indonesian Nursing Outcomes Standards (SLKI) and the Indonesian Nursing Intervention Standards (SIKI). There are still many hospitals that have not switched according to the recommendations of the nursing law. There is still completeness of nursing care documentation that is not up to the standards of the Ministry of Health. Objectives: To describe a comparative study of the completeness of nursing care documentation in the application of documentation based on Nanda NIC NOC and IDHS, SLKI, SIKI. Methods: This comparative study was conducted in the Inpatient Room of Malingping Hospital and Serang City Hospital in April-June 2022 with a total sampling of 80 nurses and 80 medical records that were selected randomly. The observation sheet is used to record the completeness of the documentation. Data were analyzed using independent t test and multiple linear regression multivariate analysis. Results: Completeness of documentation for 3S 90.74% and Nic NOc 74.04%. There is a difference in the completeness of the documentation with a p value of 0.000. Conclusion: 3S documentation is more complete than Nic Noc